Food security – an exaggerated concept - Pastorino, Leonardo Fabio (Przegląd Prawa Rolnego, 2020)
In Spanish, Italian and probably also in many other languages, the expression “seguridad alimentaria” may be understood in two ways: “food safety” or “food security.” For each of these terms, there are different definitions, each with a very different scope and relationships. Food security includes access to food, stability, nutritional values, safe food and cultural preferences. The aim of this article is to present the various aspects of this broad concept, and to demonstrate the difficulty of achieving appropriate standards for each of the components of “seguridad alimentaria.” Aspects related to food protection and so-called food self-sufficiency are also addressed. Finally, the food security paradigm has been confronted with the food safety paradigm.